2009
DOI: 10.1177/1088767908330833
|View full text |Cite
|
Sign up to set email alerts
|

Homicide-Suicide in the Netherlands

Abstract: Homicides followed by the suicide of the perpetrator are a rare yet very serious form of interpersonal violence that occurs mainly in partnerships and families. No systematic research on homicide-suicide has ever been conducted in the Netherlands. This study provides an overview of the international homicide-suicide literature. Additionally, this article describes, for the first time, the incidence and patterns of homicide-suicide in the Netherlands and compares these to homicides not followed by suicide. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 60 publications
7
62
1
Order By: Relevance
“…A departure from existing literature was noted regarding the relatively equal gender distribution among both suicidal and non-suicidal perpetrators. This contradicts findings from a national study on homicide-suicide (Liem, Postulart, & Nieuwbeerta, 2009) as well as studies conducted elsewhere, finding a higher proportion of men committing filicide-suicide. This over-representation of women among suicidal perpetrators could be attributed to relatively less lethal suicide methods employed by women, independent of their level of suicidal intent (Denning, Conwell, King, & Cox, 2000).…”
Section: Discussioncontrasting
confidence: 73%
“…A departure from existing literature was noted regarding the relatively equal gender distribution among both suicidal and non-suicidal perpetrators. This contradicts findings from a national study on homicide-suicide (Liem, Postulart, & Nieuwbeerta, 2009) as well as studies conducted elsewhere, finding a higher proportion of men committing filicide-suicide. This over-representation of women among suicidal perpetrators could be attributed to relatively less lethal suicide methods employed by women, independent of their level of suicidal intent (Denning, Conwell, King, & Cox, 2000).…”
Section: Discussioncontrasting
confidence: 73%
“…This finding agrees with that reported by Stack (1997), who reported a mean age of 35.0 yr. for those murdered in a homicide-suicide event regardless of sex and a mean age of 32.2 yr. for all other homicide victims. In contrast, Liem, et al (2009) reported the mean age of homicide victims in 103 homicide-suicides in -It should be noted that independent t tests and effect sizes are based on t tests despite not meeting the assumption that the victims' ages represent a probability sample of some larger population. The data, while a part of a larger population, were not randomly drawn from that larger population so mean differences by race and sex across homicide-suicides were compared with those on homicides alone.…”
Section: Discussionmentioning
confidence: 85%
“…Liem, et al (2009) reported the mean age of the homicide victims in uxoricide-suicides was 43 yr. and in filicide-suicides 5 yr. These results suggest the relatively younger mean age of males and older mean age of females killed in homicide-suicides may be representative of populations which differ by three or four years from the mean ages of male and female victims of homicide, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies on homicide subtypes relating to the relationship between victim and perpetrator include studies on intimate partner homicides (De Boer 1990;Fuldauer 1994), child homicides (Brants & Koenraadt 1998;Liem & Koenraadt 2008a;Verheugt 2007) and multiple family homicides (Liem & Koenraadt 2008b), homicide-suicides (Liem 2010;Liem & Koenraadt 2007;Liem, Postulart & Nieuwbeerta 2009), parent homicides (Koenraadt, 1996), homicides against prostitutes (Van Gemert 1994b), and homicides against older homosexual men (Van Gemert 1994a). Other homicides outside the family realm, such as homicides in connection with arguments have hardly been studied .…”
Section: The Netherlandsmentioning
confidence: 99%